The Correlation between Alexithymia with Gender among Nursing Students - Iyus Yosep; Rachmawati Kusuma Wardani; Ahmad Yamin; Zahrul Insan Sismayadi; Ai Mardhiyah; Rohman Hikmat (Poltekkes Kemenkes Semarang, 2023)
Background: alexithymia is a psychological condition characterized by the inability to recognize and express emotions verbally or non-verbally. People who experience alexithymia often have difficulty identifying and expressing their emotions appropriately and clearly.Purpose: the purpose of this study was to determine relationship of alexithymia with gender among nursing students in Universitas Padjadjaran.Methods: the population of this study was active students in the Bachelor's program of the Faculty of Nursing, Universitas Padjadjaran, Jatinangor/Garut and Pangandaran campus, who experienced social media addiction and are in the class of 2017, 2018, 2019, and 2020. The instrument used was the Toronto Alexithymia Scale-20 (TAS-20). Total sample was 590 students. This instrument was an instrument containing 20 statement items used to assess the level of alexithymia.Results: based on the results of the analysis of the data obtained, there is a relationship between the alexithymia level variable and gender with a sig value relationship. with a positive correlation coefficient value of 0.285, which means that the strength of the relationship between the two variables is sufficient.Conclusion: there is an adequate and positive relationship between gender and the level of alexithymia among nursing students in Universitas Padjadjaran.